Long-Term Azithromycin Treatment in Pediatric Primary Ciliary Dyskinesia: A Retrospective Study - Guan, Yuhong; Zhang, Xiang; Yang, Haiming; Xu, Hui; Zhao, Shunying (Frontiers in Pediatrics, 2022)
Objectives: Primary ciliary dyskinesia (PCD) is a rare genetic disease mainly involved in lung dysfunction. PCD patient outcomes after azithromycin (AZM) treatment have rarely been reported. This study was aimed to assess AZM treatment effects on disease progression of pediatric PCD patients. Study design: This retrospective follow-up study involved PCD patients diagnosed from 2009 to 2021. Changes of clinical outcomes, pulmonary function, and chest computed tomography findings were compared between untreated and AZM-treated patients. Results: Of 71 enrolled patients (median follow-up duration of 3.1 years), 34 received AZM (AZM-treated group) and 37 received no AZM (AZM-untreated group). At diagnosis, no significant intergroup differences in age, sex, height, weight, number of respiratory exacerbations , and FEV1% and FVC% predicted values were found, although FEF25-75% predicted was lower in AZM-treated group. Between treatment initiation and follow-up, patients in AZM-treated group had less respiratory exacerbations than that of controls (mean±SD, 1.4 ± 0.8 VS 3.0 ± 2.1, times/year P = 0.001) and fewer AZM-treated group patients exhibited exercise intolerance. Increases above baseline of AZM-treated group FEV1% and FVC% predicted values exceeded corresponding control increases, but intergroup differences were insignificant (FEV1% predicted: (median, IQR) 5.3 [-13.4, 9.4] VS 1.8 [-12.1, 9.5], P = 0.477; FVC% predicted: (median, IQR) 6.7 [-7.6, 18.8] VS 1.6 [-5.6, 7.6], P = 0·328). Conclusions: Long-term AZM treatment can reduce respiratory infection frequency and may maintain pulmonary diseases stable in pediatric PCD patients with worse lung function.